Analisis Hukum Islam tentang Perbuatan Zina dalam Pasal 284 Kitab Undang-Undang Hukum Pidana dalam Pembaharuan Hukum Pidana - Ishak Ishak (Universitas Syiah Kuala, 2012)
ABSTRACT: Islamic view on adultery concept in Article 284 of the Indonesian Penal Act is more limited compared to the concept of it in Islamic law. In addition, the reaction of criminal law towards the perpetrator in Article 284 of the Act is too lenient as it only charges by prisonment maximally 9 months. Consequently, the punishment as wording in the article has not had suffering impact towards the violator. Therefore, it should be transformed the Islamic law elements into article and its punishment in order to create the concept of Article 284 regarding Adultery in Indonesian Criminal Law revision. Islamic Law Analysis Regarding Adultery in Article 284 of The Indonesian Penal Act in Criminal Revision